2022
DOI: 10.3390/jmse10091168
|View full text |Cite
|
Sign up to set email alerts
|

Primary Composition and Pigments of 11 Red Seaweed Species from the Center of Portugal

Abstract: Macroalgae have been regarded as a natural food source since ancient times, their nutritional value being not only proven by recent studies, but also triggering further in-depth research efforts on the matter. The present study aims to provide an insight into the nutritional potential of selected red seaweed species collected in central Portugal by specifically comparing the moist yield and ash content, crude protein, total lipids, carbohydrates and pigment content between species and, ultimately, finding out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 123 publications
0
5
1
Order By: Relevance
“…In the literature, values from 4.71% [ 44 ] to 53.54% [ 45 ] are reported for the Gracilaria species. In general, the carbohydrate content obtained in this study was lower than those reported in other studies [ 46 , 47 , 48 ]. In this work, the seaweeds were characterized and directly used in the SSF without a previous washing stage.…”
Section: Resultscontrasting
confidence: 90%
“…In the literature, values from 4.71% [ 44 ] to 53.54% [ 45 ] are reported for the Gracilaria species. In general, the carbohydrate content obtained in this study was lower than those reported in other studies [ 46 , 47 , 48 ]. In this work, the seaweeds were characterized and directly used in the SSF without a previous washing stage.…”
Section: Resultscontrasting
confidence: 90%
“…Balboa et al [ 51 ] indicated that protein content exhibited a negative relationship with temperature and salinity. Overall, the macroalgal protein is considered an excellent source of EAAs and represents almost half of the total AAs they produce [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, WD40 proteins have been associated with ethylene and methyl jasmonate signaling in Grateloupia imbricata , suggesting that higher gene expression is also connected to different signals related to both the disclosure and development period of cystocarps (Garcia‐Jimenez et al., 2017; Garcia‐Jimenez, Llorens, et al., 2018; Garcia‐Jimenez, Montero‐Fernández, & Robaina, 2018). Also, we identified a female‐biased gene that annotated to R‐phycoerythrin, which is a well‐known red fluorescent pigment photosynthesis‐related protein involved in the light‐harvesting (Freitas et al., 2022). This result supports our prior identification of photosynthesis‐related proteins, including R‐phycoerythrin in Asparagopsis taxiformis female gametophytes, suggesting that added energy requirements are necessary for females during reproductive events (Patwary et al., 2023).…”
Section: Discussionmentioning
confidence: 99%